Regulation of mild cognitive impairment associated with liver disease by humoral factors derived from the gastrointestinal tract and MRI research progress: a literature review - Sun, Tianning; Feng, Maohui; Manyande, Anne; Xiang, Hongbing; Xiong, Jun; He, Zhigang (Frontiers in Neuroscience, 2023)
Patients with liver disease are prone to various cognitive impairments. It is undeniable that cognitive impairment is often regulated by both the nervous system and the immune system. In this review our research focused on the regulation of mild cognitive impairment associated with liver disease by humoral factors derived from the gastrointestinal tract, and revealed that its mechanisms may be involved with hyperammonemia, neuroinflammation, brain energy and neurotransmitter metabolic disorders, and liver-derived factors. In addition, we share the emerging research progress in magnetic resonance imaging techniques of the brain during mild cognitive impairment associated with liver disease, in order to provide ideas for the prevention and treatment of mild cognitive impairment in liver disease.